Office Treatment of Hemorrhoids - Rudd, William W.H. (1987)
The author holds that the weight of evidence from experience with 20,000 patients indicates overwhelmingly that the office treatment of hemorrhoids by means of ligation and the cryosurgical technique described is the treatment of choice. He gives 10 reasons, most of which are to the benefit of the patient, but some of which also benefit the doctor. The cost saving amounts to millions of dollars, a factor that should be of interest to government and insurers. The author suggests that operative hospital hemorrhoidectomy should no longer be performed.